Single stimulus evoked potential estimation using adaptive noise cancelling with reference alignment - Stefanelli, María Cristi; D’Alvano, Francisco; Regidor, Juan Claudia; Adrián de Pérez, Trina (Rev. Téc. Fac. Ing. Univ. Zulia)
The objective of this work is to improve Evoked Potential (EP) estirnation trough the use of an adaptive noise canceller with an enhanced reference signal. Averaging several EPs is a common method: it produces better results when the signal has been ’period-lo-period’ aligned by the maximization of Its cross-correlation with a pattern signal. A disadvantage of the averaging method is the large number of stimuli need d to get a good visualization of a useful EP. We use a two channel adaptive canceller to obtain single stimulus evoked potentials. The canceller reference signal is the quasi-periodic extension of an average EP over a few periods, aligned by cross-correlating It with the primary signal. The Widrow-Hoff LMS algorithm is used to determine the filter weights by the noisy steepest descent method. The described technique was applied to simulated signals based on actual registers obtained from visually stimulated subjects. The proposed adaptive cancellation technique provides, with fewer stimuli, better individual estimates, permitting the analysis of the EPs variability between stimuli.